PENDIDIKAN KESEHATAN MENGENAI PENATALAKSANAAN ASI DAN UPAYA MENINGKATKAN PRODUKSI ASI - Etty Komariah Sambas; Enok Nurliawati (Nindikayla Institute, 2023)
Breastmilk is the first natural food which is the main source of nutrition for babies which contains all the energy and nutrients that babies need in the first months of life. The success of exclusive breastfeeding is influenced by various factors, such as mother's education, commitment to breastfeeding, social support, mother's age, mother's knowledge, place of delivery and culture. Various studies have shown that mother's knowledge regarding breastfeeding management and efforts to increase milk production is in the range of insufficient and sufficient. Therefore, this community service activity was aimed to increase the knowledge and skills of parents and families regarding the management of breast milk and efforts to increase milk production. The method implemented was counseling and demonstration regarding the management of expressed breast milk, breastfeeding techniques and oxytocin massage. The target of the activity was parents and families of newborns who were treated at Perinatology ward at dr. Soekardjo Hospital in Tasikmalaya. The results showed that there was an increase in knowledge scores on the pre and post tests and participants could demonstrate management of expressed breast milk, breastfeeding techniques and oxytocin massage